The Future of Islamic Banking in India - Gupta, Amit (Indian Journal of Finance, 2010)
The rhythm and the swiftness with which number of Islamic Banks are coming up across the world have astonished many banking experts. Many international banks like Citi Bank, HSBC Bank, Standard Chartered Bank, etc. have already opened Islamic Banking divisions across the world, especially in several West Asian countries, Europe and USA.All this has eventually made it worthwhile to study the reasons for their incredible expansion and progress. Through this paper, an attempt has been made to find out the reasons for their growth and development and to find out their outstanding features. Islamic banking refers to a method of banking that is based on Islamic Law (Sharia) which prohibits ’interest based banking’ and permits only ’profit sharing based banking’. The concept is based on a verse of the Holy Quran that says "Allah has allowed only legitimate trade and prohibits interest". It is against interest as interest is believed to lead to exploitation and unproductive income.